Does experience matter? The relationship between nephrologist characteristics and end stage kidney disease patient outcomes. Issue 1 (5th July 2021) - Reule, Scott; Foley, Robert; Shaughnessy, Daniel; Drawz, Paul; Ishani, Areef; Rosenberg, Mark
Abstract: Background: Nephrology offers the unique opportunity to directly link patients to providers, allowing the study of patient outcomes at the provider level. The purpose of this analysis was to determine whether nephrologist experience, defined as years in nephrology practice, was associated with clinical outcomes. Design: Physician data contained within the American Medical Association (AMA) Physician Masterfile was combined with patient and Medicare claims data from the United States Renal Data System (USRDS) for the calendar year 2012, with follow up extending through June 30, 2014. Associations with important healthcare outcomes including mortality in patients receiving maintenance renal replacement therapy (RRT), waitlisting for kidney transplantation, and receipt of a kidney transplant were determined with broad adjustment for both patient and provider level variables, with attention on tertile of provider time in practice. Results: We identified 256, 324 patients on maintenance RRT cared for by 6193 nephrologists. Nephrologists with the least experience were more likely to be female, reside in a region with ≥1, 000, 000 people, have a Doctor of Osteopathic Medicine degree, and have a listed maintenance of certification status as "yes." Overall, 30.2% of the cohort died at a mean follow up of 1.99 years. Compared to those with the 0–10 years of experience, receipt of care from nephrologists with more experience was associated with lower mortality (AHR 0.97 CI 0.94–0.99 for nephrologists with 11–20 years) and increased listing for kidney transplantation (AHR 1.10; CI 1.01–1.21 for nephrologists with >21 years experience). Experience level did not result in a difference in kidney transplantation rates. Conclusions: Receipt of maintenance RRT from nephrologists with greater experience was associated with decreased mortality and increased listing for kidney transplantation, an effect that remained significant after multiple adjustments for important patient and nephrologist variables.